PRODUCTION OF FERTILIZER BY APPLYING GOOD AGRUCULTURE PRACTICES (GAP) IN TIRTA ARUM FARMER GROUP - Aditama, Ryzal Satria; Athirah, Aldila Mawanti; Sanaba, Hardiman Faramit; Puspitasari, Reza Ayu; Duwith, Alfian Markus (LPPM Univ. Ibn Khaldun Bogor, 2024)
The purpose of this program is to increase the knowledge and skills of farmer group members in making compost and liquid organic fertilizer, as well as increasing knowledge related to the application of GAP to increase production in developing and supporting the existing community economy, especially members of the Tirta Arum farmer group. The method applied in the service activity consists of several stages of activities including field surveys, socialization stages, focus group discussions (FGDs) and training, as well as monitoring and evaluation of program success. From this activity, it can be seen that the production capacity of compost and liquid organic fertilizer has increased as a business activity development of the Tirta Arum farmer group. Previously, the production of compost fertilizer reached 1 ton and liquid organic fertilizer 400 liters every month. After the activity, the production of compost reached 2 tons and liquid organic fertilizer 450 liters per month. The application of GAP in making compost and liquid organic fertilizer shows an increase in productivity. Tirta Arum farmer group is able to optimize existing resources to produce compost and liquid organic fertilizer.